Pengaruh Pemberian Reward Dan Punishment Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Intervening (Studi Pada KSPPS BMT Assyafi’iyah Berkah Nasional Kota Gajah) - Alvira Dwi Umami; Jati Imantoro; Faiz Dwi Nugroho (Jurnal Manajemen DIVERSIFIKASI, 2025)
Competition between companies now does not only involve competition for physical evidence and capital but competition for personnel or human resources owned, because competition and competition are increasingly tight, employees are required to be able to perform well. At KSPPS BMT Asyafii'iyah Berkah Nasional Kota Gajah certainly requires employees who have good performance, this can be influenced by rewards, punishments and also work discipline applied to this company. This study aims to determine the direct influence between Reward and Punishment on Employee Performance with Work Discipline as an Intervening Variable (Study on KSPPS BMT Assyafi'iyah Berkah Nasional Kota Gajah). This research is a quantitative research by measuring the variables of Reward, Punishment, Employee Performance and Work Discipline using questionnaires. The questionnaire scoring scale on each variable is 1-5 so that theoretically the range of scores obtained by respondents is between 20-100. Data collection was carried out by distributing questionnaires to a sample of 40 respondents. Data analysis in this study used path analysis with the help of SPSS application version 25. The results showed that 1) There is a direct effect of reward on employee performance. 2) There is a direct influence of punishment on employee performance. 3) There is a direct effect of reward on work discipline. 4) There is a direct influence of Punishment on employee Work Discipline. 5) There is a direct influence of Work Discipline on employee performance.